Phage vB_PaeS-PAJD-1 Rescues Murine Mastitis Infected With Multidrug-Resistant Pseudomonas aeruginosa - Wang, Zhaofei; Xue, Yibing; Gao, Ya; Guo, Mengting; Liu, Yuanping; Zou, Xinwei; Cheng, Yuqiang; Ma, Jingjiao; Wang, Hengan; Sun, Jianhe; Yan, Yaxian (Frontiers in Cellular and Infection Microbiology, 2021)
Pseudomonas aeruginosa is a Gram-negative pathogen that causes a variety of infections in humans and animals. Due to the inappropriate use of antibiotics, multi-drug resistant (MDR) P. aeruginosa strains have emerged and are prevailing. In recent years, cow mastitis caused by MDR P. aeruginosa has attracted attention. In this study, a microbial community analysis revealed that P. aeruginosa could be a cause of pathogen-induced cow mastitis. Five MDR P. aeruginosa strains were isolated from milk diagnosed as mastitis positive. To seek an alternative antibacterial agent against MDR, P. aeruginosa, a lytic phage, designated vB_PaeS_PAJD-1 (PAJD-1), was isolated from dairy farm sewage. PAJD-1 was morphologically classified as Siphoviridae and was estimated to be about 57.9 kb. Phage PAJD-1 showed broad host ranges and a strong lytic ability. A one-step growth curve analysis showed a relatively short latency period (20 min) and a relatively high burst size (223 PFU per infected cell). Phage PAJD-1 remained stable over wide temperature and pH ranges. Intramammary-administered PAJD-1 reduced bacterial concentrations and repaired mammary glands in mice with mastitis induced by MDR P. aeruginosa. Furthermore, the cell wall hydrolase (termed endolysin) from phage PAJD-1 exhibited a strong bacteriolytic and a wide antibacterial spectrum against MDR P. aeruginosa. These findings present phage PAJD-1 as a candidate for phagotherapy against MDR P. aeruginosa infection.